Performance Comparison of Bilayer and Multilayer OLED - Uniyal, Akanksha; Mittal, Poornima (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*276.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976903);" role="presentation">Active <span dir="ltr" style="left: calc(var(–scale-factor)*102.98px); top: calc(var(–scale-factor)*276.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.993808);" role="presentation">Matrix organic light emitting displays are emerging as the display of the future due to their active <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933849);" role="presentation">contribution towards the flat panel display technology. Organic light emitting displays have all the features due <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946624);" role="presentation">to which it dominates the flat panel display technology. The AMOLED displays have various features like low <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996418);" role="presentation">cost, low power consumption, high brightness, wide view angle, good color contrast and its ability to be <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00079);" role="presentation">fabricated on a flexible substrate. The display is basically an array of independently controllable pixels. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00966);" role="presentation">Therefore, the number of pixel depends on the dimension as well as on the resolution for the required <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970294);" role="presentation">application. This paper defines the types of OLED on the basis of its mode of operation (Active matrix and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986233);" role="presentation">Passive matrix). Different characteristics and parameters of individual OLED structure are extracted and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*382.03px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97797);" role="presentation">compared to show their structure dependent behavior. Undoubtedly a higher performance is achieved for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*395.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94041);" role="presentation">multilayer OLED structure with respect to the bilayer due to a significant increase in the carrier recombination <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*408.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875121);" role="presentation">rate